Blink : the power of thinking without thinking - Gladwell, Malcolm (New York : Back Bay Books Little, Brown and Co., 2005)
How do we think without thinking, seem to make choices in an instant--in the blink of an eye--that actually aren't as simple as they seem? Why are some people brilliant decision makers, while others are consistently inept? Why do some people follow their instincts and win, while others end up stumbling into error? And why are the best decisions often those that are impossible to explain to others? Drawing on cutting-edge neuroscience and psychology, the author reveals that great decision makers aren't those who process the most information or spend the most time deliberating, but those who have perfected the art of filtering the very few factors that matter from an overwhelming number of variables.
Keywords: Decision making; Intuition